EFFECTS OF READERS THEATRE AND RECIPROCAL TEACHING STRATEGIES ON STUDENTS’ LEARNING OUTCOMES IN PROSE LITERARY TEXTS IN IBADAN METROPOLIS, NIGERIA (2017)
Literature-in-English is taught in Nigerian secondary schools to develop students’ literary competence and language proficiency. However, students’ achievement in and attitude to Literature-in-English are below par in Ibadan metropolis. This has been partly attributed to students’ deficiency in prose literature. Earlier studies focused largely on teachers’ and students’ factors influencing students’ learning outcomes in prose literature with little emphasis on interventions that could make students engage and come into literary texts. This study, therefore, determined the effects of Readers Theatre and Reciprocal Teaching strategies on students’ achievement in and attitude to prose literature in Ibadan metropolis, Nigeria. The moderating effects of gender and English language proficiency were also examined. Carl Rogers’s Attribution and I.A.Richards’s Readers response theories provided the framework while the study adopted the pretest-posttest control group quasi-experimental design using a 3×2×3 factorial matrix. Purposive sampling technique was used to select six senior secondary schools in Ibadan metropolis based on the criteria of being co-educational and reading the current prescribed prose literature. An intact class of Senior Secondary School II Literature-in-English students was selected from each school. The resultant six intact classes were randomly assigned to experimental and control groups. One hundred and sixty-nine students (90 males,79 females) participated in the study. The instruments used were: Achievement test in prose literature (r=.79), Students’ attitude to prose literature-in-English Questionnaire (r=.85), English Language proficiency test (r=.81) and instructional guides. Treatment lasted twelve weeks. Data were analyse using Analysis of covariance and Scheffe post-hoc test at 0.05 level of significance. Treatment had significant main effect on students’ achievement in prose literature-in-English (F (2, 152) = 25.63; partial .25). Students in the Readers Theatre had the highest posttest achievement mean score (48.25) followed by Reciprocal Teaching (45.40) and control (19.40) groups. There was no significant main effect of treatment on students’ attitude to prose literature-in-English. English language proficiency had significant main effect on students’ achievement (F (2, 152) = 50.26; partial .40) but not on attitude. Students with high English language proficiency obtained the highest posttest mean score (68.40) followed by those in the medium (42.44) and low (18.95). The interaction effects of treatment and English language proficiency were significant on achievement but not on attitude (F (3, 152) = 32.051; partial .39). The other two-way and three-way interaction effects were not significant on achievement and attitude to prose literature-in-English. Readers Theatre and Reciprocal Teaching strategies were effective in enhancing students’ achievement in prose literature-in-English with Readers Theatre being more effective. Teachers of prose literature-in-English should adopt these strategies in their teaching delivery